2018
DOI: 10.1088/0256-307x/35/2/027102
|View full text |Cite
|
Sign up to set email alerts
|

Clustering and Dissolution of Small Helium Clusters in Bulk Tungsten

Abstract: Density functional theory calculations are conducted to investigate the stability and interactions among small helium (He) clusters in bulk tungsten (W). The lowest energy structure of each cluster for sizes n = 1 to 6 is determined. With the formation of He clusters, He defects form in bulk W. The thermodynamics of the clusters are investigated in the temperature range of 1000–2300K using molecular dynamics. This study provides the information essential to understand small He cluster behavior in bulk W.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Numerous studies have demonstrated severe tungsten degradation and the formation of a fragile, “fuzzy” surface nanostructure consisting of crystalline nanotendrils following low-energy plasma exposure. , Also, it is well-known that He clustering in He-implanted tungsten leads to the formation of immobile helium−vacancy complexes that grow to become He nanobubbles near the plasma-exposed tungsten surface, with the dynamical response of the PFC material mediated by bubble dynamics and diffusional transport of small mobile helium clusters (He n , where n ≤ 7) in the near-surface region. The formation of He nanobubbles in the near-surface region of PFC tungsten has significant impact on the material properties in this region, such as the diminishing of its thermal conductivity. , It is well-known that porosity reduces the mechanical strength and stiffness of tungsten; , consequently, the tungsten atomic density reduction in the nanobubble region by He implantation is expected to severely affect the elastic and mechanical properties of PFC tungsten. Several studies have been conducted to examine the mechanical response (strength and fracture mechanics) to He irradiation of nanocrystalline tungsten or W alloys. Nevertheless, the dependence of the elastic properties of He-implanted single-crystalline tungsten on its structural parameters, in addition to the role of He nanobubbles in the recrystallization kinetics of tungsten, as a result of plasma exposure still remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated severe tungsten degradation and the formation of a fragile, “fuzzy” surface nanostructure consisting of crystalline nanotendrils following low-energy plasma exposure. , Also, it is well-known that He clustering in He-implanted tungsten leads to the formation of immobile helium−vacancy complexes that grow to become He nanobubbles near the plasma-exposed tungsten surface, with the dynamical response of the PFC material mediated by bubble dynamics and diffusional transport of small mobile helium clusters (He n , where n ≤ 7) in the near-surface region. The formation of He nanobubbles in the near-surface region of PFC tungsten has significant impact on the material properties in this region, such as the diminishing of its thermal conductivity. , It is well-known that porosity reduces the mechanical strength and stiffness of tungsten; , consequently, the tungsten atomic density reduction in the nanobubble region by He implantation is expected to severely affect the elastic and mechanical properties of PFC tungsten. Several studies have been conducted to examine the mechanical response (strength and fracture mechanics) to He irradiation of nanocrystalline tungsten or W alloys. Nevertheless, the dependence of the elastic properties of He-implanted single-crystalline tungsten on its structural parameters, in addition to the role of He nanobubbles in the recrystallization kinetics of tungsten, as a result of plasma exposure still remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely reported that severe tungsten degradation may occur under continuous He plasma exposure through formation of a fragile, “fuzzy” surface nanostructure consisting of crystalline nanotendrils. , Helium clustering that promotes bubble formation in tungsten has been studied extensively, and it is well understood that such formation of overpressurized He bubbles in PFC tungsten has a significant impact on the material properties, such as the diminishing of its thermal conductivity and reduction of its mechanical strength. In previous studies, we reported that He bubble formation can severely affect (soften) the elastic properties of PFC tungsten, which, in turn, accelerates the rate of nanotendril formation and growth on the PFC surface. , Numerous experimental and simulation studies have been conducted to investigate the impact of He irradiation on the mechanical response of nanocrystalline tungsten and W alloys. Moreover, several studies have reported and carefully characterized the mechanical and structural response of nanoscale single-crystalline tungsten under compressive and tensile loading/unloading and examined the role of twinning and dislocation dynamics in the deformation mechanisms. , Nevertheless, the dependence of the mechanical properties of He-implanted single-crystalline tungsten on its structural parameters and the role of He nanobubbles as a result of plasma exposure in the deformation dynamics of PFC tungsten at and beyond the onset of plasticity still remain elusive.…”
Section: Introductionmentioning
confidence: 95%